Candidate Quality - Panu Poutvaara; Tuomas Takalo (Center for Economic Studies and ifo Institute (CESifo), 2003)
We analyze the topical question of how the compensation of elected politicians affects the set of citizens choosing to run. To this end, we develop a sparse and tractable citizen-candidate model of representative democracy with ability differences, informative campaigning and political parties. Our results suggest that primaries, campaign costs and rewards have previously overlooked interactions that should be studied in a unified framework. Surprisingly, increasing the reward may lower the average candidate quality when the campaigning costs are sufficiently high. The model accommodates a variety of extensions of which we study costly primaries, two-stage signalling, and ideological differences.
Keywords: 330; politicians' competence; career concerns; campaigning costs; rewards for elected officials; citizen-candidate models